Functions of the bonus-malus system in the motor third party liability insurance of motor vehicle owners - Anna Szymańska (Economic and Environmental Studies (E&ES), 2018)
The bonus-malus system is one of the stages of the ratemaking process in motor liability insurance. The purpose of the work is to discuss the role of the bonus-malus systems in the ratemaking and to present their functions. The article reviews the measures for assessment of the ratemaking function of the bonus-malus systems and attempts to investigate the impact of preventive and marketing functions. These functions fulfil their role under the condition that the insured party is aware of the functioning of the bonus-malus system. It has been hypothesized that the policyholders choosing the insurer do not know the bonus-malus system offered to them and that increasing the knowledge about the functioning of the system intensifies the impact of its preventive function. The study was conducted on the basis of an analysis of the insurance conditions offered by the insurers on the Polish market (GIT) and a questionnaire survey. Mathematical statistics methods have been used for the analysis. The results of the research confirm the hypothesis that the insured do not know the bonus-malus system while choosing an insurer. This is the effect of not passing enough information to the client. The results allow claiming that even offering brief information about the rules of the functioning of the bonus-malus system improves the awareness of policyholders and increases the impact of the preventive function, which makes it possible to positively verify the second research hypothesis.
Keywords: G22; C11; C51; 330; bonus-malus system; motor third party liability insurance